Spin-Wave-Driven Skyrmion Motion in Magnetic Nanostrip - Guangfu Zhang; Ye Tian; Yangbao Deng; Dongchu Jiang; Shuguang Deng (Journal of Nanotechnology)
The photon-assisted magnetic recording utilizes the ultrafast laser to excite the spin wave in the magnetic nanostructures and accordingly switch its magnetization state. Here, by means of micromagnetic simulation, the motion of magnetic skyrmions, a topologically protected chiral magnet with few nanometer size, induced by the spin wave is studied. It is found that the magnetic skyrmion can move in the same direction of spin-wave propagation, which is first accelerated and then decelerated exponentially. The magnetic skyrmion motion originated from the robust coupling of the spin waves with the skyrmion, through the SW’s linear momentum transfer torque acting on the skyrmion. Besides amplitude, the reflectivity of the spin wave by skyrmion has tremendous impact on the velocity of skyrmion motion. The skyrmion velocities are mainly determined by the reflectivity, when the spin-wave amplitude is almost identical. Our results give guidance for the design and development of spin-wave control spintronics.